The Internalization of Religious Values in Organizational Culture to Foster a Harmonious Work Environment in Madrasahs: A Systematic Literature Review - arum Wardatul Husna Asyauqiya; Prim Masrokan Mutohar; Zahrotur Roifah (JIEM (Journal of Islamic Education Management), 2026)
This study aims to systematically review the literature on the internalization of religious values within organizational culture as an effort to create a harmonious work climate in madrasah. Using a systematic literature review (SLR) approach, 15 relevant articles/journals were identified and analyzed based on three clusters of research questions: (Q1) concepts and strategies for internalizing religious values, (Q2) implementation of religious values in madrasah organizational culture, and (Q3) the impact of religious culture on harmonious work climate. Findings indicate that effective internalization requires a multidimensional approach including exemplary behavior (uswah hasanah), habituation, and environmental conditioning. Islamic value-based organizational culture supported by visionary leadership has been proven capable of establishing a conducive, harmonious, and productive work climate. These findings emphasize the importance of integrating modern management with Islamic values for sustainable madrasah quality improvement.